The Content Analysis Of English Workbook Used In SMKN 1 Gombong - Astuti, Dwi Wiji (LPPM Universitas Mercu Buana Yogyakarta, 2017)
The research belongs to content analysis which focused on analyzing English workbook content used for grade ten in SMKN 1 Gombong. In analyzing the workbook, the researcher considered the five aspects ofÂ standardized book suggested by Hutchinson and Waters (2003): audience, aims, content, methodology, and other criteria. The objective of this research was to find out the quality level of English workbook content based on the criteria of standardized book proposed by Hutchinson and Waters (2003). The instruments used in this research were interview, observation, and documentation. The researcher applied both qualitative and simple quantitative method for this research. Qualitative was used for analyzing and delivering the result into depth description; meanwhile, simple quantitative was for computation result of analysis in a form of number. Based on the result of the research, the workbook was in the fair level, also the researcher viewed that the workbook included into a less standardized book. It was proven by the total scoring of analysis that the workbook reached the number of 35. After doing analysis, the workbook used for grade ten in SMKN 1 Gombong contains of General English.